2016
DOI: 10.3109/10428194.2015.1108415
|View full text |Cite
|
Sign up to set email alerts
|

Sequential DICE combined withl-asparaginase chemotherapy followed by involved field radiation in newly diagnosed, stage IE to IIE, nasal and extranodal NK/T-cell lymphoma

Abstract: Extranodal natural killer (NK)/T-cell lymphoma is an aggressive lymphoid tumor. Optimal treatment strategies have not yet been fully defined. To explore a more effective treatment, we conducted sequential chemoradiotherapy (SCRT) and evaluated the safety and efficacy. Seventy-eight patients (51 males, 27 females) were analyzed. The complete response (CR) rate was higher for patients in the SCRT group (90.9%) than in the radiotherapy group (77.8%; p = 0.124). The relapse rate (RR) and death rate (DR) were lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…61 The ORR was 100%, with CR achieved These data show that with the use of effective chemotherapy, there is no difference between concomitant or sequential radiotherapy and chemotherapy. For most institutes, sequential chemotherapy and radiotherapy is logistically easier to arrange.…”
Section: Sequential Chemotherapy and Radiotherapymentioning
confidence: 84%
“…61 The ORR was 100%, with CR achieved These data show that with the use of effective chemotherapy, there is no difference between concomitant or sequential radiotherapy and chemotherapy. For most institutes, sequential chemotherapy and radiotherapy is logistically easier to arrange.…”
Section: Sequential Chemotherapy and Radiotherapymentioning
confidence: 84%
“…VIPD is an effective and well-tolerated treatment regimen for early-stage ENKTCL patients [8,22]. A phase II study consisting of 30 stage I/II ENKTCL patients demonstrated that 100% of patients achieved a response to VIPD chemotherapy, with 3-year PFS and OS rates of 85.19% and 86.28%, respectively [22].…”
Section: Discussionmentioning
confidence: 99%
“…With a median follow-up of 63.2 months, the 5-year OS and PFS were 85 and 74% [72]. In a retrospective analysis, 33 patients with stage I/II disease were treated with 4 cycles of DICE-L-asp (dexamethasone, ifosfamide, cisplatinum, etoposide, and L-asparaginase), followed by radiotherapy as consolidation [73]. The ORR was 100%, with CR achieved in 90.9%.…”
Section: Introductionmentioning
confidence: 99%